2007
DOI: 10.1021/ef700250g
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Catalysts for Biodiesel Production

Abstract: The production of biodiesel is greatly increasing due to its enviromental benefits. However, production costs are still rather high, compared to petroleum-based diesel fuel. The introduction of a solid heterogeneous catalyst in biodiesel production could reduce its price, becoming competitive with diesel also from a financial point of view. Therefore, great research efforts have been underway recently to find the right catalysts. This paper will be concerned with reviewing acid and basic heterogeneous catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
355
0
25

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 725 publications
(388 citation statements)
references
References 72 publications
8
355
0
25
Order By: Relevance
“…This is because of heterogeneous catalysts have different phases of the substrate so it is easy to be separated [2]. One of the base catalysts which often used in the reaction are metal oxide catalysts such as CaO, MgO or other alkaline metal oxide [3]. However, the metal oxide catalysts are more expensive than metal hydroxides such as NaOH.…”
Section: Introductionmentioning
confidence: 99%
“…This is because of heterogeneous catalysts have different phases of the substrate so it is easy to be separated [2]. One of the base catalysts which often used in the reaction are metal oxide catalysts such as CaO, MgO or other alkaline metal oxide [3]. However, the metal oxide catalysts are more expensive than metal hydroxides such as NaOH.…”
Section: Introductionmentioning
confidence: 99%
“…When the use of mixtures is allowed, they can be obtained by direct transesterification of fats and oils using either acid [4] or basic [5] catalysts. On the contrary, when the final application requires the use of a pure fatty acid ester, or free fatty acids are present in large amount in the triglycerides mixtures, the synthetic method of choice is the esterification of the fatty acid using an acid catalyst [6].…”
Section: Introductionmentioning
confidence: 99%
“…Lopez et al [17] employed MgO calcined at 600°C, but reached only 18% conversion of the oil feedstock, due to the low surface area of the catalyst. Di Serio et al [18] reported the highest yield of 90%, using 12:1 methanol to oil ratio, a temperature of 180°C, and a reaction time of 60 min with 5.0 wt% of the catalyst in batch conditions. Dossin et al [15] evaluated the use of MgO in batch and continuous stirred tank reactors at industrially relevant conditions: the results indicated that MgO worked efficiently in a batch-reactor at ambient temperature, and therefore reactor heating was not required.…”
Section: Heterogeneous Catalystmentioning
confidence: 99%